Distant readings of disciplinarity : knowing and doing in composition/rhetoric dissertations - Miller, Benjamin (Poet) (Writing research, pedagogy, and policy., 2022)
"In Distant Readings of Disciplinarity, Miller brings a big data approach to the study of disciplinarity in rhetoric, composition, and writing studies by developing maps of the methods of RCWS dissertations from 2001 to 2015. Combining charts with engaging prose, Miller offers a model of how large-scale data-driven research can advance disciplinary understanding"--